Trends in the Utilization of BRCA1 and BRCA2 Testing After the Introduction of a Publicly Funded Genetic Testing Program. - Dossa, Fahima; Baxter, Nancy N.; Sutradhar, Rinku; Little, Tari; Velsher, Lea; Lerner-Ellis, Jordan; Eisen, Andrea; Metcalfe, Kelly (Current Oncology, 2025)
Simple Summary: When utilized effectively, genetic testing for cancer risk-increasing mutations, (such as pathogenic mutations in the BRCA1 and BRCA2 genes) can identify high-risk individuals prior to cancer development, allowing for tailored interventions aimed at early cancer detection and prevention. In this study of trends in BRCA1 and BRCA2 testing after the implementation of a publicly funded testing program in Ontario, Canada, we demonstrate increasing utilization of testing over time. However, we find that testing largely focused on women with cancer and that testing has not increased among cancer-free women who stand to gain the most from cancer risk-reducing interventions. With greater accessibility to germline genetic testing, this study highlights the need for targeted strategies to identify and test high-risk individuals before cancer development. Purpose: To effectively reduce cancer burden, genetic testing programs should identify high-risk individuals prior to cancer development, when risk-reduction strategies can be implemented. We evaluated trends in BRCA1/BRCA2 testing use after implementation of a publicly funded testing program. Methods: We conducted a retrospective, near population-based study of women who underwent BRCA1/BRCA2 testing in Ontario, Canada, (2007–2016) (n = 15,986). Temporal trends were evaluated using linear and Poisson regression. Results: Although annual utilization of testing increased over time (p < 0.001), mean age at testing increased from 49.9 years (SD 13.8) in 2007 to 53.8 years (SD 13.7) in 2016 (p < 0.001). The proportion of women with a cancer history at testing also increased from 53.5% in 2007 to 66.3% in 2015 (p < 0.001); the proportion of women free from breast cancer did not change significantly (49.2% in 2007 versus 45.1% in 2015, p = 0.90). As a proportion of all tested, those with breast cancer tested within 3 months of diagnosis increased over time (0.39% of tests in 2007 versus 13.6% of tests in 2015; p < 0.001). Conclusions: While the institution of a publicly funded genetic testing program was associated with rising utilization, increasing age at testing and decreasing testing of unaffected women suggest limitations in identifying high-risk individuals eligible for risk-reduction.